A heuristic algorithm for the auto-carrier loading problem. (2016) - Chen, Huey-Kuo
This paper studies the auto-carrier loading problem (ACLP) formulated as an integer mathematical programming model in which the associated objective function seeks to minimise the total number of reloads along the scheduled auto-carrier route. This study makes necessary modification of the previous Agbegha et al.'s (1998) formulation. A heuristic algorithm is then proposed and demonstrated in detail with nine instances that have appeared in the literature. The nine instances are the various loading results for examples assigning vehicles on different auto-carrier configurations and, for each configuration, taking into consideration constraints imposed by different types of vehicle. Computational experiments indicate that the proposed heuristic algorithm is superior to Agbegha et al.'s (1998) method by obtaining better or at least the same quality solutions.